Legal Approach of Female Domestic Workers in India: Issues and Challenges (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Female domestic workers constitute a neglected group in the unorganized sector of India. They have faced exploitation for decades. In recent years, only Non-Governmental Organizations have expressed concern about their well-being. This paper looks at the challenges and emerging issues associated with the female domestic workers of India. They are very vulnerable in terms of human rights, in particular their living and working conditions. There are lots of problems faced by female domestic workers at workplace, which includes- low wages, excess work burden, no extra pay for extra work, no holidays or leaves, sexual harassment by male employer etc. Over the decades, though demand for these female domestic workers has increased but their issues and problems are still same. There is not much improvement in their working and living conditions.